SPE Middle East Oil and Gas Show and Conference 2007
DOI: 10.2118/105166-ms
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Water–Producing Zones While Underbalanced Drilling Horizontal Wells—Integration of Sigma Log and Real–Time Production Data

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe paper presents a novel logging approach used to identify water producing zones while under-balanced drilling (UBD) horizontal wells. This approach will work in mixed-wet reservoirs and is particularly attractive for mature reservoir undergoing waterflooding.The logging process consists of a standard logging-whiledrilling (LWD) data acquisition followed by a pulse neutron capture run (PNC). The PNC data is acquired after pumping the tool inside the drillpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…A similar behavior of the resistivity index curves has been reported by Gauthier et al (2007) for the Cretaceous carbonate reservoirs in Oman as shown in Fig. 2.…”
Section: Resistivity Hysteresis In Carbonatessupporting
confidence: 86%
See 1 more Smart Citation
“…A similar behavior of the resistivity index curves has been reported by Gauthier et al (2007) for the Cretaceous carbonate reservoirs in Oman as shown in Fig. 2.…”
Section: Resistivity Hysteresis In Carbonatessupporting
confidence: 86%
“…Hysteresis in the resistivity index as observed byGauthier et al (2007). Typical production test data for case study well; flowrate and pressure on the left and the pressure derivative on the right.…”
mentioning
confidence: 88%
“…al. 13 show how corroborating UBD data with resistivity data can lead to valuable information on reservoir permeability. Their approach represents the most sophisticated application of reservoir characterization reported in literature to date.…”
Section: Introductionmentioning
confidence: 87%
“…al. 13 emphasize this in their works. Because of the importance of this correlation, logging-while-drilling (LWD) is strongly recommended for every UBD well.…”
Section: Correlation To Log Datamentioning
confidence: 94%